FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN IMUNISASI PNEUMOCOCCAL CONJUGATE VACCINE (PCV ) PADA BADUTA DI PUSKESMAS JONGGOL TAHUN 2023 - angel, Angelia Subha (Jurnal Ayurveda Medistra, 2024)
ISPA prevention and Control Program carried out by the Indonesian Ministry of Health is focused on controlling pneumonia in children under five because it contributes greatly to the morbidity and mortality rates of children under five. The aim of this research is to determine the factors associated with PCV immunization visits for baduta at the Jonggol public health center in 2023. This research design used correlative or cross sectional analytical design. The result show: relationship between family support and PCV immunization visits at the Jonggol public health center show pearson Chi-square 0.002 ( < 0.05) which means there is have correlation between family support and PCV immunization visits. Meanwhile, the knowledge factors shows the person Chi-Square 0.032 ( < 0.05), which means there is no relationship between knowledge and PCV immunization visits. For the source of information factor, The pearson Chi-square result showed 0.05 ( > 0.05), which means there is no relationship between the source of information and PCV immunization visits.